2005
DOI: 10.1165/rcmb.2004-0374oc
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Elastase and Related Proteases from Human Neutrophil for Binding to α1-Protease Inhibitor

Abstract: The protease-antiprotease imbalance that is characteristic of most inflammatory lung disorders depends on the spatial-temporal regulation of active inhibitor and protease concentrations in lung secretions. We have studied the competition between the three main serine proteases from human neutrophil primary granules in their binding to alpha1-Pi, the main serine proteases inhibitor in lung secretions. Elastase was the only target of alpha1-Pi when identical molar amounts of purified inhibitor and the three prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 41 publications
3
61
0
Order By: Relevance
“…Our finding that stoichiometric amounts of ␣1-Pi almost completely inhibit mHNE agrees with our recent finding that the inhibitor binds essentially to HNE, and not to Pr3 or cathepsin G, although these potential targets for this inhibitor are also present at the cell surface (26). This is explained, at least in part, by the different rate constants for association and by the two-step mechanism of Pr3 inhibition that could favor HNE binding when competition occurs (47).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding that stoichiometric amounts of ␣1-Pi almost completely inhibit mHNE agrees with our recent finding that the inhibitor binds essentially to HNE, and not to Pr3 or cathepsin G, although these potential targets for this inhibitor are also present at the cell surface (26). This is explained, at least in part, by the different rate constants for association and by the two-step mechanism of Pr3 inhibition that could favor HNE binding when competition occurs (47).…”
Section: Discussionsupporting
confidence: 91%
“…No HNE activity was detected in crude BALF, suggesting that both free HNE and mHNE are controlled by endogenous inhibitors, as previously shown by Western blotting (26). However, the BALF neutrophils were morphologically identical with activated blood neutrophils, and flow cytometry showed thet they bore CD63 on their FIGURE 4.…”
Section: Inhibition Of Mhne Activity Of Unfixed and Fixed Neutrophilssupporting
confidence: 52%
See 1 more Smart Citation
“…␣1-PI is an excellent irreversible inhibitor of HNE that also inhibits related neutrophil proteases PR3 and CG. ␣1-PI inhibits HNE with a inhibitor/enzyme stoichiometry of 1, whereas that with PR3 and CG is slightly higher because of partial proteolytic inactivation of some inhibitor molecules occurring during the course of the interaction (Duranton and Bieth, 2003;Korkmaz et al, 2005b). The second-order constants of association of ␣1-PI with HNE, PR3, and CG are 6.5 ϫ 10 7 , 8.1 ϫ 10 6 , and 4.1 ϫ 10 5 M Ϫ1 ⅐ s…”
Section: A Serine Protease Inhibitorsmentioning
confidence: 99%
“…However, selective inhibitors of NE have not been fully effective in controlling neutrophil-mediated damage in the airways [11], supporting the likelihood that other proteinases play a role. Further, KORKMAZ et al [12] have suggested that A1AT preferentially inhibits NE, and that PR3 is only inhibited after NE is completely neutralised, suggesting that PR3 may play a more important role when both are released.…”
mentioning
confidence: 99%